2021 Joseph W. Richards Fellowship – Summary Report: Toward On-Chip Electronic Monitoring of Bacterial Conjugation. (December 2021) - Butler, Derrick
Abstract : Intercellular conjugation is a primary communication method by which bacteria transfer genetic material from one cell to another. Because conjugation mediates the transfer of genetic material, it enables the spread of antibiotic resistance and other virulence factors within a population. Current techniques for its study have low throughput and require extensive sample preparation, making real-time monitoring of conjugation dynamics challenging.To address these shortcomings, we are exploring two-dimensional (2D) materials as a strain-sensitive platform for on-chip, electronic monitoring of conjugation events.